General chemistry: principles and modern applications - Petricci, Ralph H. (Upper Saddle River, New Jersey : Prentice-Hall, 2002)
For this new edition, we have tried to follow this important advice to writers by attending more to the needs of those students who are taking a serious journey through the material.